The narrow road towards a possible decriminalisation of consensual sodomy in Malawi - Kumitengo, Josephine Lucia (Department of Public Law, 2015)
The study is comprised of five chapters, with this as the first and will proceed on the hypothesis that criminalisation of consensual sodomy is unconstitutional and should be invalidated even in the midst of challenges to such a declaration. Chapter two will give comprehensive outline of the offence of carnal knowledge against the order of nature under section 153 of the Code. The ambiguities created by section 153 are analysed in chapter three where a critical discussion on the case of Republic v Steven Monjeza Soko and Tionge Chimbalanga Kachepa will also be made. A constitutional analysis of section 153 (a) and (c) will be done and it will be argued that it impairs the rights to equality, privacy and dignity in a manner that is indefensible. Chapter four will highlight among others, how the requirement of locus standi in constitutional cases is a limitation to the constitutionality challenge of section 153 (a) and (c). It will also show how the current Malawi setup of the appointing judges of the High court by the Chief Justice to sit as a constitutional court is another hindrance to the decriminalisation of the provision. In addition, the possibilities of decriminalising the offence of sodomy will be explored. Chapter five is the concluding remarks and recommendations.